(Invited) Enhancing Phase Stability and CO2 Tolerance of Ba0.5Sr0.5Co0.8Fe0.2O3-δ. (31st August 2017) - Ivers-Tiffée, Ellen; Almar, Laura; Szász, Julian; Meffert, Matthias; Störmer, Heike; Gerthsen, Dagmar
Abstract : The effect of B-site cation substitution on the phase stability of Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF) in O2 - and CO2 -containing atmospheres has been studied thoroughly by our group. In particular, a doping concentration of 10 mol-% yttrium (Y) was found to strongly reduce or suppress secondary phase formation extending the stability of the cubic phase regime. Characterization by electrochemical impedance spectroscopy (EIS) of both, pure and Y-doped BSCF electrodes, is performed in oxygen-nitrogen mixtures as well as in CO2 -containing atmospheres using symmetrical SOFC cells with Ce0.9 Gd0.1 O2-δ (CGO) as electrolyte from 600 to 900 °C. Analysis of the EIS data in combination with the distribution of relaxation times (DRT) reveals an enhanced tolerance of the Y-doped BSCF cathodes towards the adsorption of CO2 molecules. The enhanced stability of the cubic phase and reduced poisoning effect on the oxygen reduction reaction in CO2 - containing atmospheres by doping, is further confirmed by scanning electron microscopy (SEM) and analytical (scanning) transmission electron microscopy ((S)TEM) combined with energy dispersive X-ray spectroscopy (EDXS).